Tetrazine bioorthogonal chemistry derived in vivo imaging - Zhao, Gaoxiang; Li, Zhutie; Zhang, Renshuai; Zhou, Liman; Zhao, Haibo; Jiang, Hongfei (Frontiers in Molecular Biosciences, 2022)
Bioorthogonal chemistry represents plenty of highly efficient and biocompatible reactions that proceed selectively and rapidly in biological situations without unexpected side reactions towards miscellaneous endogenous functional groups. Arise from the strict demands of physiological reactions, bioorthogonal chemical reactions are natively selective transformations that are rarely found in biological environments. Bioorthogonal chemistry has long been applied to tracking and real-time imaging of biomolecules in their physiological environments. Thereinto, tetrazine bioorthogonal reactions are particularly important and have increasing applications in these fields owing to their unique properties of easily controlled fluorescence or radiation off-on mechanism, which greatly facilitate the tracking of real signals without been disturbed by background. In this mini review, tetrazine bioorthogonal chemistry for in vivo imaging applications will be attentively appraised to raise some guidelines for prior tetrazine bioorthogonal chemical studies.